2011
DOI: 10.1080/19440049.2010.551422
|View full text |Cite
|
Sign up to set email alerts
|

Residual concentrations of the flukicidal compound triclabendazole in dairy cows’ milk and cheese

Abstract: Triclabendazole (TCBZ) is a flukicidal halogenated benzimidazole compound extensively used in veterinary medicine. Liver fluke control in lactating dairy cattle is difficult because treatment should be implemented only during the dry period to avoid milk residues. However, control in endemic areas is usually implemented as regular treatments three to four times a year, even during the lactating period. Thus, information on TCBZ milk excretion and the risk of the presence of drug residues in fluid milk and milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…However, in endemic areas, parasite control programmes are implemented as regular anthelmintic treatments, even during the lactating period (Imperiale et al, 2011). In these situations, concomitant administration of multiple drugs would be likely to lead to modifications in secretion of drugs and other ABCG2 substrates, such as some vitamins, into milk (van Herwaarden et al, 2007), with an important effect on milk quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in endemic areas, parasite control programmes are implemented as regular anthelmintic treatments, even during the lactating period (Imperiale et al, 2011). In these situations, concomitant administration of multiple drugs would be likely to lead to modifications in secretion of drugs and other ABCG2 substrates, such as some vitamins, into milk (van Herwaarden et al, 2007), with an important effect on milk quality.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions for HPLC analysis of TCBZ metabolites were modified in accordance with Imperiale et al (2011). Oxibendazole (Sigma-Aldrich) was used as an internal standard and samples were extracted with acetonitrile.…”
Section: High Performance Liquid Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it ideal for the cheese-making process. However, in the final dairy products, drug residues can be concentrated (De Liguoro et al 1996;Imperiale et al 2011). After treating with veterinary drugs, the risks associated with milk residues may be present, bearing in mind that the primary control of residues is by adherence to label withdrawal period statements (Imperiale et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nitroxynil (NIT, 3‐iodo‐4‐hydro‐5‐nitrobenzonitrile), a halogenated phenol, is widely applied to control immature and adult liver flukes in cattle and sheep . Meanwhile, NIT can be firmly bound to plasma proteins with a bonding rate greater than 98%, thus it has a long half‐life time in animals . Furthermore, numerous studies have confirmed that NIT can be a persistent residue in milk .…”
Section: Introductionmentioning
confidence: 99%